Skład chemiczny odcieków z odpadów przed i po mechaniczno - biologicznym przetworzeniu - Suchowska-Kisielewicz, Monika
The reduction of the waste removed to landfill, including particularly waste that are biodegradable, is the basic objective in the scope of waste management of the first decade of the 21st century. European Council Directive on the Landfill of Waste 1999/31/WE is of special importance. It obliges Poland to reduce the amount of storage of biodegradable waste with the reference to the mass produced in 1995 by: 25% by year 2010, 50% by year 2013 and 65% by year 2020. The objective can be achieved through mechanical and biological treatment (MBT) of municipal waste before storage. Data on chemical composition and the amount of leachate from mono-landfills of biologically treated municipal waste is limited. Chemical composition and the amount of leachate and biogas that are removed from waste before and after MBT treatment landfilled in technical scale and in laboratory with and without leachate recirculation were presented in the thesis.
Keywords: odcieki, recyrkulacja, odpady komunalne, mechaniczno-biologiczne przetwarzanie odpadów komunalnych (MBP), stałe kinetyczne szybkości rozkładu odpadów